A case report of reactive hypoglycemia in a patient with pheochromocytoma and it′s review of literature - Rajesh Patnaik Thonangi; Minaxi Bhardwaj; Bindu Kulshreshtha (Indian Journal of Endocrinology and Metabolism, 2014)
Pheochromocytoma, a tumor characterized by catecholamine excess, is usually associated with impaired glucose tolerance. Hypoglycemia may occur after the abrupt withdrawal of catecholamines in the postoperative period. Rarely, insulin secretion by stimulation of β-2 adrenoreceptors may overwhelm the glucagon production, thereby causing hypoglycemia. Here, we describe a female with pheochromocytoma, who presented with postprandial hypoglycemia.